Tissue engineering of the peripheral nerve : biomaterials and physical therapy - Geuna, Stefano (International review of neurobiology, 2013)
This issue of International Review of Neurobiology brings together cutting-edge research on tissue engineering of the peripheral nerve. It reviews current knowledge and understanding, provides a starting point for researchers and practitioners entering the field, and builds a platform for further research and discovery.This volume covers the cutting-edge research on tissue engineering of the peripheral nerve.